2019
DOI: 10.3390/w11051082
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Urban Flood Resilience in an Uncertain Future

Abstract: Preliminary results of the UK Urban Flood Resilience research consortium are presented and discussed, with the work being conducted against a background of future uncertainties with respect to changing climate and increasing urbanization. Adopting a whole systems approach, key themes include developing adaptive approaches for flexible engineering design of coupled grey and blue-green flood management assets; exploiting the resource potential of urban stormwater through rainwater harvesting, urban metabolism mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…The method has been tested in Carshalton (London Borough of Sutton), exploring and prioritising a series of potential pathways and developing a roadmap for adaptation over the next 40 years (Figure 3). This combines hydrodynamic modelling to identify when service thresholds are exceeded and trigger further intervention, and evaluation (monetised and spatial incorporating a real options approach) of the multiple benefits of different BG þ G pathways (Gersonius et al 2015;Manocha & Babovic 2017;Fenner et al 2019). Additional criteria beyond a standard cost benefit analysis (CBA) form part of the decision-making process.…”
Section: Theme 1: Engineering Design To Enhance Service Delivery (Wp1)mentioning
confidence: 99%
See 2 more Smart Citations
“…The method has been tested in Carshalton (London Borough of Sutton), exploring and prioritising a series of potential pathways and developing a roadmap for adaptation over the next 40 years (Figure 3). This combines hydrodynamic modelling to identify when service thresholds are exceeded and trigger further intervention, and evaluation (monetised and spatial incorporating a real options approach) of the multiple benefits of different BG þ G pathways (Gersonius et al 2015;Manocha & Babovic 2017;Fenner et al 2019). Additional criteria beyond a standard cost benefit analysis (CBA) form part of the decision-making process.…”
Section: Theme 1: Engineering Design To Enhance Service Delivery (Wp1)mentioning
confidence: 99%
“…good and bad words) based on reaction times. IATs have been used in environmental research evaluating, for example, implicit connectedness with nature (Liu et al 2019), and are being trialled by the UFR Consortium to help identify some of the underlying implicit attitudes towards the use of blue, green and grey space that may exert a significant influence on public preferences (Fenner et al 2019).…”
Section: Theme 3: Flood Risk Management At the Heart Of Urban Planninmentioning
confidence: 99%
See 1 more Smart Citation
“…Campisano et al [4] recognized that there is a shortage of high-quality datasets relating to water savings and stormwater management and identified a need for improved modelling to quantify and assess these dual benefits. In the UK, the Urban Flood Resilience research consortium has identified RWH as key multifunctional infrastructure which can decrease surface water flooding [5]. However, the majority of these systems are still focused solely on the potential for water conservation without considering other potential benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Community resilience is identified as recovering from urban flood hazards quickly [41]. However, the loss data are difficult to obtain at the community scale.…”
Section: Validationmentioning
confidence: 99%